Investigation of Edge-Selectively Nitrogen-Doped Metal Free Graphene for Oxygen Reduction Reaction - Huan, He; Qingwei, Yang; Shaohua, Xiao; Xiaoyan, Han; Qin, Li; Kangle, Lv; Jingping, Hong; Dingguo, Tang; Deng, Kejian (Journal of Advances in Nanotechnology, 2020)
In order to distinguish the roles of four types of nitrogen species in oxygen reduction reaction, the ketoamine condensation reactions between the ketone group of graphene oxide and amidogen of aniline and o-phenylenediamine were employed to generate –C=N- bond at the edge of graphene nanoplatelets, and then nitrogen-doped graphene nanoplatelets with pyrrolic N, pyridinic N and pyridinic N+-O- rather than graphitic nitrogen were obtained by post thermal treatments. The resulting catalysts were characterized by X-ray diffraction analysis, X-ray photoelectron spectroscopy and electrochemical measurements. It is found that edge-selectively nitrogen-doped graphene nanopaltelets with nitrogen content of up to 4.28 atom% have been prepared. Nitrogen doping helps to improve activity of oxygen reduction reaction slightly, suggesting nitrogen doping at the edge of graphene does not contribute a lot to the enhancement of activity.
Keywords: Edge selectivity; Nitrogen doping; Graphene; Oxygen reduction reaction; Ketoamine condensation reaction